2001
DOI: 10.1093/fampra/18.5.540
|View full text |Cite
|
Sign up to set email alerts
|

Reflections from organization science on the development of primary health care research networks

Abstract: In the UK, policy changes in primary health care research and development have led to the establishment of primary care research networks. These organizations aim to increase research culture, capacity and evidence base in primary care. As publicly funded bodies, these networks need to be accountable. Organizational science has studied network organizations including why and how they develop and how they function most effectively. This paper draws on organizational science to reflect on why primary care resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
(22 reference statements)
0
32
0
Order By: Relevance
“…Therefore, PCRNs represent a great diversity of network models, objectives, and configurations. 12,13 In general, PCRNs aim to conduct research close to practice, identify and respond to current primary care research needs, and to engage more primary care professionals with research. In addition to these researchbased objectives, it has been suggested that PCRNs can also play an important role in the translation and diffusion of research findings into practice 14 -16 and other activities that are relevant in the field of Internationally, both policy advisers and researchers have acknowledged the importance of PCRNs and have recognized the challenging opportunities they provide for the improvement of primary care.…”
Section: Abstract: Practice-based Research Pbrn Evaluationmentioning
confidence: 99%
“…Therefore, PCRNs represent a great diversity of network models, objectives, and configurations. 12,13 In general, PCRNs aim to conduct research close to practice, identify and respond to current primary care research needs, and to engage more primary care professionals with research. In addition to these researchbased objectives, it has been suggested that PCRNs can also play an important role in the translation and diffusion of research findings into practice 14 -16 and other activities that are relevant in the field of Internationally, both policy advisers and researchers have acknowledged the importance of PCRNs and have recognized the challenging opportunities they provide for the improvement of primary care.…”
Section: Abstract: Practice-based Research Pbrn Evaluationmentioning
confidence: 99%
“…These related but powerful interlinked themes are stipulated in paragraph 1, article 7 of Alma-Ata (2). According to Fenton et al, health service research pioneered within PHC is a central strategy for new planning to achieve attainable health (41). PHC, as suggested earlier, is primarily a hub of the health sector, providing contact between patients and networks in the research and development process.…”
Section: The Role Of Phc In Improving Access To Medicines In Context mentioning
confidence: 99%
“…30 The socialisation involved in networks is essential for transferring the tacit knowledge that frequently distinguishes high performance teams. 31 "Trust, in itself, becomes an asset that group members can rely on more generally to help solve problems of cooperation and coordination." (page 543) 31 Expertise networks between services enable comparison of experiences and practices by those who know their intimate detail, and facilitate the sharing of opinions about how to deal with new developments.…”
Section: The Value Of Networkmentioning
confidence: 99%
“…31 "Trust, in itself, becomes an asset that group members can rely on more generally to help solve problems of cooperation and coordination." (page 543) 31 Expertise networks between services enable comparison of experiences and practices by those who know their intimate detail, and facilitate the sharing of opinions about how to deal with new developments. Networks are central to quality management, and in particular, "Benchmarking encourages each unit to take control of its own destiny, and yet to learn collaboratively from competitor and ally alike."…”
Section: The Value Of Networkmentioning
confidence: 99%
See 1 more Smart Citation